Short-term care strategy in a cesarean section patient with pulmonary hypertension, EF 25% and intraventricular thrombus: A case report - Novella Syafrita; Vera Muharrami; Novita Anggraeni; Nopian Hidayat (Science Midwifery, 2026)
Cesarean section in patients with pulmonary hypertension and interventricular septal thrombus is a high-risk condition that requires an integrated care strategy and multidisciplinary preparation. The primary goals of care are to ensure hemodynamic stability, control pulmonary artery pressure, and prevent thromboembolic complications during and after surgery. Prior to the procedure, patients are prepared with careful anticoagulation therapy using heparin, strict fluid management, and oxygenation support. The choice of anesthetic is made considering its impact on pulmonary pressure and right heart function. Invasive monitoring, such as arterial lines and central venous pressure (CVP), is used intraoperatively for close monitoring. Collaboration between the obstetrics, anesthesia, cardiology, and intensive care teams is crucial to minimize maternal and fetal risks and ensure a safe cesarean section.